Teaching profession : passion and mission - Pawilen, Greg Tabios (Quezon City, Philippines : Rex Book Store, 2016)
This book is about the Teaching Profession. The teaching profession is as old as life itself. ching is an integral part of everyday life. In ancient times, parents, elders, and leaders served as teachers. These people are driven by a deep passion and a great sense of mission serve humanity by giving their lives, services, talents, skills, and wisdom to help individuals re a dignified life and discover the secrets of the universe. Every human being considers noble task to impart knowledge, share experiences, guide, advise, teach a skill, train, and mold the character of each individual.
Chapter 1. The teacher as a person in the society -- Chapter 2. Teaching competencies -- Chapter 3. Challenges in teaching -- Chapter 4. Legal bases of the teaching profession.
Includes bibliographical references and index.
Keywords: TEACHING -- PASSION -- MISSION